2016
DOI: 10.15835/nsb839831
|View full text |Cite
|
Sign up to set email alerts
|

<i>In-vitro</i> Antimicrobial Activity of Roots of <i>Rauwolfia serpentina</i> L. Benth Kurz

Abstract: Microbial pathogens develop resistance to antibiotics after repeated administration during the treatment of infectious diseases. Therefore, it is necessary to find alternative antimicrobial drugs and the present trend is focused on medicinal plants. The hereby research work was carried out to investigate the antimicrobial activity of solvents as well as aqueous extracts of Rauwolfia serpentina roots. The extracts were tested against Bacillus subtilis, Enterococcus faecalis, Escherichia coli, Klebsiella pneumon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
1
2
0
Order By: Relevance
“…These two solvents showed the most effective inhibition against GBS, with a mean inhibition diameter ranging from 15 mm to 23 mm. This finding aligns with the studies conducted by Eteng et al 34 and Mokutima et al 35 , but it contradicts the report by Owk & Lagudu 36 , who found that the methanol extract exhibited the highest activity against GBS. 32 , who also observed similar effects of these plants on GBS.…”
Section: Antibacterial Susceptibility Pattern Of Bioactive Fractions ...supporting
confidence: 80%
“…These two solvents showed the most effective inhibition against GBS, with a mean inhibition diameter ranging from 15 mm to 23 mm. This finding aligns with the studies conducted by Eteng et al 34 and Mokutima et al 35 , but it contradicts the report by Owk & Lagudu 36 , who found that the methanol extract exhibited the highest activity against GBS. 32 , who also observed similar effects of these plants on GBS.…”
Section: Antibacterial Susceptibility Pattern Of Bioactive Fractions ...supporting
confidence: 80%
“…The microorganisms were cultured in Nutrient Broth (beef extract 3 g, peptone 10 g, NaCl 5 g, agar 20 g, water 1 L, pH7.4‐7.6) for 16 h, under shaking . Disc diffusion method was used for screening the antimicrobial activity of all berries in order to determine the growth inhibition zones of microorganisms around certain berries . The Muller Hinton Agar (MAA) was dissolved in distilled water to make a concentration of 3.1 g/100 mL.…”
Section: Methodsmentioning
confidence: 99%
“…The increasing demand of various Rauvolfia species for medicinal uses has caused a serious reduction of the individual number in native populations due to over-exploitation, habitat loss and anthropogenic activities. As a result, several Rauvolfia species are now restricted in its natural habitat and have also been recognized as vulnerable (Owk and Lagudu 2016).…”
mentioning
confidence: 99%